The Influence of the Tourism Sector and Local Economic Development on Regional Original Income (PAD) in Central Lombok Regency - Adinda Dwi Safitri; Masrun Masrun; Ali Akbar Hidayat (Westscience Press, 2025)
This study aims to determine the influence of the tourism sector and local economic development as seen from the number of tourist visits, the number of hotel rooms, and the number of MSMEs on the Regional Original Income (PAD) in Central Lombok Regency for the period 2002-2023. This study uses secondary data obtained from the Central Statistics Agency (BPS), the Cooperatives and SMEs Service, and regional financial reports for a certain period. The analysis method used is an associative quantitative approach using time series data. The calculation uses Multiple Linear Regression Analysis, Classical Assumption Test, and Hypothesis Test. The results of the study show that the variables of the number of hotel rooms and the number of MSMEs have a positive but not significant effect, while the number of tourist visits has a positive and significant effect on the regional original income in Central Lombok Regency. Simultaneous calculations show that the independent variables have a positive and significant effect on the regional original income of Central Lombok Regency with a large influence of 91.38% and the rest is influenced by other variables.